A techno-environmental overview of a corn stover biomass feedstock supply chain for cellulosic biorefineries. Issue 1 (2nd January 2017) - Shah, Ajay; Darr, Matt; Khanal, Sami; Lal, Rattan
ABSTRACT: Corn stover is the primary feedstock choice of the first generation of cellulosic biorefineries in the Midwestern US due to its abundance in the region. The technically sound, economic and environment-friendly supply system of this feedstock is inevitable for the commercial success and proliferation of these biorefineries. Such supply systems involve different aspects of stover production, harvesting, collection, handling, transportation, storage and preprocessing. This review discusses the environmental concerns of stover collection for biofuels production, and provides an update on the technological status of the corn stover feedstock supply system. The major environmental concerns of corn stover collection discussed here include its impact on soil nitrogen availability and crop requirements, changes in crop productivity, soil erosion and change in soil organic carbon, soil fertility, carbon sequestration, nutrient emissions and disease pressures. The cellulosic biorefinery feedstock quality requirements and different supply chain components are also thoroughly discussed. This review concludes by presenting a perspective on near-term and future corn stover-based feedstock supply systems with the potential to be commercially implemented. Although the extent of stover removal from the field is highly debated, there is a consensus that some fraction of biomass removal would help lower both agronomic production cost and environmental impact.